Impact of vaccination on ICU admissions of hospitalized COVID-19 patients in a country with a heterologous vaccine policy - Süleyman Yıldırım; Cenk Kirakli; Yeliz Özdemir; Selma Tosun; Sinem Ermin; Gülru Polat; Celalettin Yılmaz; Semra Bilaçeroğlu; Bilge Salık; Berna Kömürcüoğlu; İlker Ödemiş; Şükran Köse; et al. (Journal of Infection in Developing Countries)
Introduction: Vaccination against coronavirus disease-19 (COVID-19) is highly effective in preventing severe disease and mortality. Adenoviral vector and mRNA vaccines were effective against intensive care unit (ICU) admission, but the effectiveness of inactivated vaccine on ICU admission was unclear. We aimed to evaluate the effect of vaccination status on ICU admission in hospitalized COVID-19 patients in a country with heterologous vaccination policy.